Petroleum system and formation evaluation of the Whicher Range tight gas sands - Rezaee, Reza; Saeedi, Ali; Clennell, B. (Geological Survey of Western Australia, 2012)
The Whicher Range tight gas sand field is located 280 km south of Perth in the Bunbury trough of the South Perth Basin. Gas in place estimates range up to 5 tcf and a gross gas column height of about 650m is identified for this field. However gas flow test rates have been below expectations, typically about 1 MMcfd. The main reservoir interval is the Permian Willespie Formation which occurs at a depth range of ~3800m to ~4600m. The reservoir comprises fine to coarse grained sandstones (subarkose) interbedded with siltstone, shale and coal seams. In general reservoir quality is poor, with averages of total porosity and effective porosity being 9.7% and 2% respectively. Permeability is very variable, highly stress dependent, and very low, rarely exceeding 0.3 mD under overburden conditions. Attempts to improve gas flow to a viable rate (~4 MMcfd per well) through the application of different stimulation methods, including hydraulic fracturing, acidization and underbalanced drilling, were unsuccessful. Numerous investigations have been performed previously in an endeavor to identify the controls to these poor results. This study reviewed the previous investigations and conducted new core and log measurements to re-evaluate the Willespie Formation in terms of reservoir quality and petroleum systems analyses.